CCNP security firewall 642-618 official cert guide - Hucaby, Dave (Cisco Press, 2012)
Trust the best selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for exam success. They are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. CCNP Security FIREWALL 642-618 Official Cert Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. "Do I Know This Already?" quizzes open each chapter and enable you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. · Master Cisco CCNP Security FIREWALL exam topics · Assess your knowledge with chapter-opening quizzes · Review key concepts with exam preparation tasks · Practice with realistic exam questions on the CD-ROM CCNP Security FIREWALL 642-618 Official Cert Guide , focuses specifically on the objectives for the CCNP Security FIREWALL exam. Expert networking consultants Dave Hucaby, Dave Garneau, and Anthony Sequeira share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. The companion CD-ROM contains a powerful Pearson IT Certification Practice Test engine that enables you to focus on individual topic areas or take a complete, timed exam. The assessment engine also tracks your performance and provides feedback on a module-by-module basis, laying out a complete assessment of your knowledge to help you focus your study where it is needed most. Well-regarded for its level of detail, assessment features, comprehensive design scenarios, and challenging review questions and exercises, this official study guide helps you master the concepts and techniques that will enable you to succeed on the exam the first time. The official study guide helps you master all the topics on the CCNP Security FIREWALL exam, including: ASA interfaces IP connectivity ASA management Recording ASA activity Address translation Access control Proxy services Traffic inspection and handling Transparent firewall mode Virtual firewalls High availability ASA service modules CCNP Security FIREWALL 642-618 Official Cert Guide is part of a recommended learning path f...
Includes bibliographical references and index. - Print version record
Keywords: Electronic data processing personnel -- Study guides -- Certification; Computer networks -- Study guides -- Security measures -- Examinations; Firewalls (Computer security) -- Study guides -- Examinations; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Coupe-feu (Sécurité informatique); Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Electronic data processing personnel; Certification; Engineering & Applied Sciences; Computer Science; Study guides